2021
DOI: 10.1111/cas.14710
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic features and poor prognostic factors of interstitial lung disease with nivolumab for non–small cell lung cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The patient who died after a relapse had a non–DAD‐like pattern at initial ILD and at time of relapse but had progressed to a DAD‐like pattern before death. This was consistent with our primary manuscript, which showed that a DAD‐like pattern is one of the poor prognostic factors 8 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The patient who died after a relapse had a non–DAD‐like pattern at initial ILD and at time of relapse but had progressed to a DAD‐like pattern before death. This was consistent with our primary manuscript, which showed that a DAD‐like pattern is one of the poor prognostic factors 8 …”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with our primary manuscript, which showed that a DAD-like pattern is one of the poor prognostic factors. 8 The main strength of this study is that it examined patients with NSCLC who were treated with nivolumab and experienced ILD in a real-world setting, and, therefore, the data are generalizable to the Japanese population. This study also had a sufficiently large sample size, and ILD-related data for each patient were carefully assessed by a group of experts to ensure that the ILD experienced by patients was due to nivolumab treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate was significantly higher in the group with the DAD pattern (DAD, 53.3% vs. non-DAD, 13.3%). Among the previous reports, only one observational study examining nivolumab-induced DILD reported the DAD pattern as a statistically significant predictor of a poor prognosis (Saito et al 2020 ). The high mortality rate in patients with the DAD pattern agrees with the findings of previous reports on DILD (40–83.3%) (Gemma et al 2014 , 2019 , 2020 ; Shi et al 2014 ; Hotta et al 2010 ; Tomii et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%